2010
DOI: 10.1037/a0020766
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of web-based personalized normative feedback: A two-year randomized controlled trial.

Abstract: Objective Web-based brief alcohol interventions have the potential to reach a large number of individuals at low cost; however, few controlled evaluations have been conducted to date. The present study was designed to evaluate the efficacy of gender-specific versus gender-nonspecific personalized normative feedback (PNF) with single versus biannual administration in a 2-year randomized controlled trial targeting a large sample of heavy-drinking college students. Method Participants included 818 freshmen (57.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
214
2
17

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(245 citation statements)
references
References 62 publications
12
214
2
17
Order By: Relevance
“…In 5 trials rated as low to moderate risk of bias in students (37,48,49,52), e-interventions resulted in no statistically significant reduction in binge drinking (MD, −0.1 episodes [CI, −0.6 to 0.4]) at 6-month follow-up. Effect sizes had moderate heterogeneity (Q = 8.8; P = 0.066; I 2 = 55%); 1 trial rated as low risk of bias that studied human support reported significant effects (44).…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…In 5 trials rated as low to moderate risk of bias in students (37,48,49,52), e-interventions resulted in no statistically significant reduction in binge drinking (MD, −0.1 episodes [CI, −0.6 to 0.4]) at 6-month follow-up. Effect sizes had moderate heterogeneity (Q = 8.8; P = 0.066; I 2 = 55%); 1 trial rated as low risk of bias that studied human support reported significant effects (44).…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…PNF interventions have been shown to reduce drinking from 1 month (Dimeff & McNeely, 2000;Doumas et al, 2009) to 2 years (Neighbors et al, 2010) after baseline. The success of PNF may be a function of multiple underlying mechanisms; however, correction of normative misperceptions has been emphasized as the primary mediating mechanism underlying PNF and other social norms-based alcohol interventions (e.g., Burchell et al, 2013;Lewis & Neighbors, 2006).…”
Section: P Ersonalized Normative Feedback (Pnf)mentioning
confidence: 99%
“…Interventions based on this approach attempt to address commonly held misperceptions of peer norms and reduce the perceived social pressure to engage in heavy consumption by providing feedback comparing students' perceptions of social norms at their university with actual campus norms (McAlaney et al, 2011). There is evidence that social norms-focused feedback interventions are effective in reducing student alcohol use and perceptions of peer norms (e.g., Neighbors et al, 2010). Although few social norms interventions have focused on reducing cannabis use, preliminary research has indicated the potential benefits of web-based personalized normative feedback on reducing perceived peer descriptive and injunctive cannabis use norms (Elliott & Carey, 2012;Lee et al, 2010).…”
mentioning
confidence: 99%